2013
DOI: 10.1590/s1516-35982013000700005
|View full text |Cite
|
Sign up to set email alerts
|

Digestible lysine levels in diets for laying Japanese quails

Abstract: -The objective of this study was to estimate the digestible lysine requirement of Japanese quails in the egg-laying phase. A total of 336 female Japanese quails (Coturnix coturnix japonica) of average initial age of 207 days were distributed in a completely randomized experimental design, composed of 6 treatments (lysine levels) with 7 replicates and 8 birds per experimental unit, with duration of 84 days. Experimental diets were formulated from a basal diet, with corn and soybean meal, with 2.800 kcal ME/kg a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
1
8
0
2
Order By: Relevance
“…The same behavior was observed for the intake of lysine per bird (p < 0.05), indicating an increase of 10.256 grams of lysine per bird for each 0.1% increase in the lysine level, as determined by equation with R 2 = 99.81%, SSR=1.8 and AIC=13.08. Similar results were reported by Ton et al (2011), Ribeiro et al (2013), Nery et al (2015) and Lima et al (2016), who found, for Japanese quail, a linear behavior with precision of 99%, 100%, 98% and 98%, respectively.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The same behavior was observed for the intake of lysine per bird (p < 0.05), indicating an increase of 10.256 grams of lysine per bird for each 0.1% increase in the lysine level, as determined by equation with R 2 = 99.81%, SSR=1.8 and AIC=13.08. Similar results were reported by Ton et al (2011), Ribeiro et al (2013), Nery et al (2015) and Lima et al (2016), who found, for Japanese quail, a linear behavior with precision of 99%, 100%, 98% and 98%, respectively.…”
Section: Resultssupporting
confidence: 89%
“…Ton et al (2011) verified linear behavior with 93% of precision power for feed conversion in European quail. Barreto et al (2006) and Della-Flora et al (2012) found, in European quails, that there was no difference in feed conversion per mass in relation to the different levels of digestible lysine, and the same was found by Costa et al (2008), Ribeiro et al (2013) and Nery et al (2015) for Japanese quails.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…In our other study, investigating the optimal amino acid supplementation for Japanese quail, a three-week period was necessary for adaption (unpublished). Furthermore, in other Japanese quail studies, the data collection has spanned long periods ranging from 84 to 140 days , Ribeiro et al, 2013. Therefore, the greater expression of the AP and NAP behaviors at day 14 of the experiment is most likely the result of the adaptation period of these birds…”
Section: Discussionmentioning
confidence: 99%